Properties of a potassium channel in cultured human gastric cells (HGT-1) possessing specific omeprazole binding sites. Issue 10 (October 1993) - Sandle, G I; Fraser, G; Fogg, K; Warhurst, G
Abstract : The HGT-1 human gastric cell line is similar to acid secreting parietal cells in that it possesses H2 receptors, histamine sensitive adenyl cyclase, and Cl- channels, which are activated by histamine by a cyclic adenosine monophosphate (cAMP) dependent mechanism. To discover if HGT-1 cells have additional properties found in parietal cells, [3H]omeprazole and patch clamp recording techniques were used to evaluate specific omeprazole binding sites and K+ channels in the plasma membrane. HGT-1 cells exhibited [3H]omeprazole binding in the non-stimulated state, which increased 100% in the presence of 1 mM histamine. High conductance (about 155 pS) K+ channels were active spontaneously in 17% of cell attached or excised inside out patches in non-stimulated subconfluent HGT-1 cells. In inside out patches, channel activity increased fivefold during depolarisation, ion substitution experiments confirmed that the channels were highly selective for K+, and channel activity was almost abolished by removal of Ca2+ or addition of 5 mM Ba2+. In quiescent cell attached patches, 0.1 mM dibutyryl cAMP failed to activate K+ channels. In contrast, 6.7 microM A23187 (a Ca2+ ionophore) increased intracellular Ca2+ concentration from mean (SEM) 14 (3) nM to 248 (30) nM and activated K+ channels in 21% of patches. It is concluded that the plasma membrane of HGT-1 cells possesses (a) specific 3H-omeprazole binding sites, which may reflect the omeprazole sensitive H+, K(+)-ATPase present in gastric parietal cells; and (b) Ca(2+)-activated K+ channels, which may be located in the basolateral membrane of human gastric parietal cells and play a part in acid secretion triggered by Ca(2+)-mediated secretory agonists.